Molecular Mechanisms of Glucose Fluctuations on Diabetic Complications - Zhang, Zhen-Ye; Miao, Ling-Feng; Qian, Ling-Ling; Wang, Ning; Qi, Miao-Miao; Zhang, Yu-Min; Dang, Shi-Peng; Wu, Ying; Wang, Ru-Xing (Frontiers in Endocrinology, 2019)
Accumulating evidence indicates the occurrence and development of diabetic complications relates to not only constant high plasma glucose, but also glucose fluctuations which affect various kinds of molecular mechanisms in various target cells and tissues. In this review, we detail reactive oxygen species and their potentially damaging effects upon glucose fluctuations and resultant downstream regulation of protein signaling pathways, including protein kinase C, protein kinase B, nuclear factor-κB and the mitogen-activated protein kinase signaling pathway. A deeper understanding of glucose-fluctuation-related molecular mechanisms in the development of diabetic complications may enable more potential target therapies in future.